Effect of Ni3Sn4 on the Thermo-Mechanical Fatigue Life of Solder Joints in 3D IC - Zhang, Liang; Zhong, Su-Juan (Frontiers in Materials, 2021)
In this paper, Ni/Sn/Ni joints simulated the 3D integration was carried out by TLP bonding (250°C, 0.2 N) with different bonding time. After TLP bonding, planner-type Ni3Sn4 IMC can be observed, when the bonding time is 180min, complete Ni3Sn4 can be found. The diffusion coefficient D can be determined to be 32.4μm2/min. Based on finite element simulation, it is demonstrated that the shear stress and creep strain increases obviously with the increase of IMC thickness, the results calculated show that the IMC thickness can impact the fatigue life of solder joints significantly, with the increase the Ni3Sn4 thickness, the fatigue life of solder joints can be decreased obviously.